A Gendered Discourse Analysis of Biological and Trans-Women’s Narratives on Women’s History Month Celebration - Montecillo, Althea B.; Bonaoy, Jessica L.; Aperocho, Maico Demi B. (Future Science / FSH-PH Publications, 2025)
This research paper presents a comparative analysis of the narratives from biological and trans women regarding the inclusion of trans women in celebrating Women's History Month. Utilizing Labov and Waletzky's Structural Approach to Narrative, the study examines the linguistic nuances in the narratives of ten participants—five trans women advocating for inclusion (Group A) and five biological women expressing reservation about trans women’s inclusion (Group B). The analysis reveals significant differences between the two groups' use of evaluative and referential clauses. Group A's narratives predominantly feature evaluative clauses (59%), reflecting personal emotions and subjective interpretations of their experiences. Group B's narratives are characterized by a higher percentage of referential clauses (65%), focusing on their actual experiences and centering on the factual events. This disparity illustrates how each group's beliefs manifest in their narratives, highlighting the complexities of gender identity and inclusion within feminist discourse. The findings also revealed the importance of identifying referential and evaluative clauses in understanding the stances of trans and biological women, further underscoring the importance of recognizing diverse perspectives in the ongoing conversation about women's rights and the need for a deeper understanding of the implications of these differences in shaping feminist narratives. This study contributes valuable insights to the fields of feminism, linguistics, and social activism, advocating for a more inclusive dialogue that honors the experiences of all women.